2018
DOI: 10.3389/fonc.2018.00360
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nomogram for Preoperative Prediction of Early Recurrence in Intrahepatic Cholangiocarcinoma

Abstract: Introduction: The emerging field of “radiomics” has considerable potential in disease diagnosis, pathologic grading, prognosis evaluation, and prediction of treatment response. We aimed to develop a novel radiomics nomogram based on radiomics features and clinical characteristics that could preoperatively predict early recurrence (ER) of intrahepatic cholangiocarcinoma (ICC) after partial hepatectomy.Methods: A predictive model was developed from a training cohort comprising 139 ICC patients diagnosed between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 40 publications
2
91
0
Order By: Relevance
“…TENGXIANG cHEN 1,2 , SHAN LEI 1,2 , ZHIRUI ZENG 1,2 , SHUTAO PAN 3 , JINJUAN ZHANG 1,2 , YAN XUE 1,2 , YUANMEI SUN 1,2 , JINZHI LAN 1,2 , SU XU 4 , dAHUA MAO 5 and BING GUO 1,2 cells to chemotherapy via regulating AKT2 (15). Similarly, in colon cancer, patients with low expression levels of miR-137 have adverse clinical prognosis (16,17).…”
Section: Microrna-137 Suppresses the Proliferation Migration And Invmentioning
confidence: 98%
See 1 more Smart Citation
“…TENGXIANG cHEN 1,2 , SHAN LEI 1,2 , ZHIRUI ZENG 1,2 , SHUTAO PAN 3 , JINJUAN ZHANG 1,2 , YAN XUE 1,2 , YUANMEI SUN 1,2 , JINZHI LAN 1,2 , SU XU 4 , dAHUA MAO 5 and BING GUO 1,2 cells to chemotherapy via regulating AKT2 (15). Similarly, in colon cancer, patients with low expression levels of miR-137 have adverse clinical prognosis (16,17).…”
Section: Microrna-137 Suppresses the Proliferation Migration And Invmentioning
confidence: 98%
“…ccA is responsible for 5-15% of all primary liver cancer cases and is the second most frequent type of liver cancer (1). ccA is a highly invasive malignancy, exhibiting early distal organ and lymph node metastasis and resistance to chemotherapy (2,3). In recent years, the morbidity and mortality of ccA have increased worldwide (4).…”
Section: Introductionmentioning
confidence: 99%
“…However, their nomogram was solely based on clinicopathologic features without considering imaging features. Liang et al developed a radiomics nomogram to preoperatively predict early recurrence (ER) of intrahepatic cholangiocarcinoma after partial hepatectomy . They reported that the radiomics nomogram demonstrated better performance when combined with clinical features.…”
mentioning
confidence: 99%
“…A cut-off of 1 year after resection has been used in previous studies to distinguish the early and late recurrence (31,32). Patients relapsed within 1 year after initial resection may represent more aggressive tumor biology.…”
Section: Discussionmentioning
confidence: 99%